Organizational Culture, Knowledge Sharing, and Innovation’s Impact on Competitive Advantage in the Indonesian Bakery Industry - Jasmine Chiquita Brilliana; Hartoyo; Lilik Noor Yuliati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Intensifying competition and rapid changes in consumer preferences within the Indonesian bakery industry have compelled firms to continuously strengthen their internal capabilities to sustain competitive advantage. This research aims to examine the effect of organizational culture, knowledge sharing, and organizational innovation in building a competitive advantage in the bakery industry. Using the perspectives of resource-based view, knowledge-based view, and dynamic capabilities, this study adopts a sequential design of mixed-method exploration. The qualitative phase involved in-depth interviews with one director, two coordinating managers, and one manager, followed by quantitative analysis using 197 survey responses. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that organizational culture significantly influences knowledge sharing, organizational innovation, and competitive advantage. In addition, the sharing of knowledge and organizational innovation contributes significantly to competitive advantage. These findings emphasize the importance of fostering a strong organizational culture that supports knowledge sharing and innovation to achieve sustainable competitiveness.